Heterogeneity of response to immune checkpoint blockade in hypermutated experimental gliomas - Aslan, Katrin; Turco, Verena; Blobner, Jens; Sonner, Jana K.; Liuzzi, Anna Rita; Núñez, Nicolás Gonzalo; De Feo, Donatella; Vollmuth, Philipp; Fischer, Manuel; Green, Ed; Sadik, Ahmed; Friedrich, Mirco; et al. (Nature Communications, 2020)
Intrinsic malignant brain tumors, such as glioblastomas are frequently resistant to immune checkpoint blockade (ICB) with few hypermutated glioblastomas showing response. Modeling patient-individual resistance is challenging due to the lack of predictive biomarkers and limited accessibility of tissue for serial biopsies. Here, we investigate resistance mechanisms to anti-PD-1 and anti-CTLA-4 therapy in syngeneic hypermutated experimental gliomas and show a clear dichotomy and acquired immune heterogeneity in ICB-responder and non-responder tumors. We made use of this dichotomy to establish a radiomic signature predicting tumor regression after pseudoprogression induced by ICB therapy based on serial magnetic resonance imaging. We provide evidence that macrophage-driven ICB resistance is established by CD4 T cell suppression and Treg expansion in the tumor microenvironment via the PD-L1/PD-1/CD80 axis. These findings uncover an unexpected heterogeneity of response to ICB in strictly syngeneic tumors and provide a rationale for targeting PD-L1-expressing tumor-associated macrophages to overcome resistance to ICB.